Domestic Violence and Children’s Rights: An Analysis of the Duties to Good Administration of Justice and to Effective Remedies Under Articles 41 and 47 of the Charter of Fundamental Rights of the European Union and the Istanbul Convention (De Legibus - Revista de Direito da Universidade Lusófona Lisboa, 2025)
Domestic violence constitutes a grave violation of human dignity and individual rights. Unfortunately, inadequate communication and coordination between criminal and family courts often hinder the effective implementation of the Istanbul Convention. Even when interaction occurs, family court decisions can sometimes conflict with criminal convictions, leaving victims and their children without adequate protection. A striking example is the ruling of the Tribunal da Relação de Lisboa (TRL)1 of 11 January 2022,2 where the Court ordered a shared residence arrangement for a child with the abusive parent. This decision fails to comply with the Istanbul Convention, as well as with Articles 9 and 18 of the United Nations Convention on the Rights of the Child (UNCRC), Article 8 of the European Convention on Human Rights (ECHR), and Articles 41 and 47 of the Charter of Fundamental Rights of the European Union (EU Charter), as it neglects to provide effective remedies and good administration of justice for the victims involved, once the child was also a witness victim of the aggressions against the mother.